From the Headlines to Hollywood: The Birth and Boom of Warner Bros. - Yogerst, Chris (Rowman & Littlefield Publishers, 2016)
More than any other studio, Warner Bros. used edgy, stylistic, and brutally honest films to construct a view of America that was different from the usual buoyant Hollywood fare. The studio took seriously Harry Warner’s mandate that their films had a duty to educate and demonstrate key values of free speech, religious tolerance, and freedom of the press. This attitude was most aptly demonstrated in films produced by the studio between 1927 and 1941—a period that saw not only the arrival of sound in film but also the Great Depression, the rise of crime, and increased concern about fascism in the lead-up to World War II. In From the Headlines to Hollywood: The Birth and Boom of Warner Bros.,Chris Yogerstexplores how “the only studio with any guts” established the groundwork and perfected formulas for social romance dramas, along with gangster, war, espionage, and adventure films. In this book, the author discusses such films as ThePublic Enemy, Little Caesar, G-Men, The Life of Emile Zola, Angels with Dirty Faces,and Confessions of a Nazi Spy, illustrating the ways in which their plots truly were “ripped from the headlines.” While much of what has been written about Warner Bros. has focused on the plots of popular films or broad overviews of the studio’s output, this volume sets these in the larger context of the period, an era in which lighthearted fare competed with gritty realism. From the Headlines to Hollywood will appeal to readers with interests in film history, social history, politics, and entertainment.